2015
DOI: 10.1007/s11064-015-1678-y
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical, Metabolic, and Behavioral Characteristics of Immature Chronic Hyperphenylalanemic Rats

Abstract: Phenylketonuria and hyperphenylalanemia are inborn errors in metabolism of phenylalanine arising from defects in steps to convert phenylalanine to tyrosine. Phe accumulation causes severe mental retardation that can be prevented by timely identification of affected individuals and their placement on a Phe-restricted diet. In spite of many studies in patients and animal models, the basis for acquisition of mental retardation during the critical period of brain development is not adequately understood. All anima… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 95 publications
1
4
0
Order By: Relevance
“…In the largest study to date, Wasserstein et al reported that plasma phenylalanine was negatively correlated with relative cerebral glucose metabolic rates, as measured via [ 18 F]fluorodeoxyglucose positron emission tomography (PET), in ten patients with classical PKU who performed a verbal learning task during the tracer uptake period. The PKU group also had lower cortical relative glucose metabolic rate than the control group, a finding that was consistent with smaller clinical (Yanai et al, 1987;Hasselbalch et al, 1996;Ficicioglu et al, 2013) and animal studies (Qin and Smith, 2007;Dienel and Cruz, 2016).…”
Section: Introductionsupporting
confidence: 73%
“…In the largest study to date, Wasserstein et al reported that plasma phenylalanine was negatively correlated with relative cerebral glucose metabolic rates, as measured via [ 18 F]fluorodeoxyglucose positron emission tomography (PET), in ten patients with classical PKU who performed a verbal learning task during the tracer uptake period. The PKU group also had lower cortical relative glucose metabolic rate than the control group, a finding that was consistent with smaller clinical (Yanai et al, 1987;Hasselbalch et al, 1996;Ficicioglu et al, 2013) and animal studies (Qin and Smith, 2007;Dienel and Cruz, 2016).…”
Section: Introductionsupporting
confidence: 73%
“…This finding verifies that our experimental PKU model is valid and was effective in PKU formation. There are animal models of PKU using Phe and p-Cl-Phe in the literature, and studies are related to oxidative stress (Bortoluzzi et al 2019), brain energy metabolism (Dimer et al 2018), and metabolic changes (Dienel and Cruz 2016). No studies of the BDNF-CREB pathway have been reported previously.…”
Section: Discussionmentioning
confidence: 99%
“…To establish a PKU model [15][16][17], daily injection of phenylalanine (Phe) (5.2 mmol/g body weight) was used, while the phenylalanine hydroxylase inhibitor, p-chlorophenylalanine (p-Cl-Phe) (0.9 mmol /g body weight) was administered every other day (PKU group). Saline solution (saline) was administered to the control group.…”
Section: Experimental Design: Pku Modelmentioning
confidence: 99%